Practical Economics Economic Transformation and Government Reform in Georgia 2004-2012 - Gilauri, Nika (Springer Nature, 2017)
Comparative Politics; Political Economy; Public Administration; Macroeconomics; Economics; Finance; Economic Growth; Russian, Soviet, and East European History